2023
DOI: 10.1038/s41598-023-38711-8
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Citrullus lanatus var. Colocynthoides seeds in seaweed extract improved seed germination, plant growth and performance under salinity conditions

Abstract: Citrullus lanatus var. Colocynthoide “Gurum” is an unconventional crop that can be utilized as a new source of edible oil and has the ability to grow in a variety of harsh conditions. To mitigate the adverse effects of salinity on seed germination and plant performance of C. lanatus, seeds were primed in the aqueous extracts of the seaweed Ulva lactuca before planting under greenhouse conditions. The aqueous extract of U. lactuca at 8% w/v led to maximal seed germination percentage and seedling growth of C. la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The strong effect of the Codium fragile extract is probably due to the combination of these different active compounds that, through different modes of action, confer to durum wheat seedlings a greater tolerance to salt stress. Other studies reported that priming seeds with SWE leads to an improved antioxidant enzyme activity [ 42 ]. The seed coating with SWE has also led to a general reduction in germination time, especially under salt stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strong effect of the Codium fragile extract is probably due to the combination of these different active compounds that, through different modes of action, confer to durum wheat seedlings a greater tolerance to salt stress. Other studies reported that priming seeds with SWE leads to an improved antioxidant enzyme activity [ 42 ]. The seed coating with SWE has also led to a general reduction in germination time, especially under salt stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A similar positive effect on shoots and roots was observed also in other crops such as tomato, okra, etc. [ 36 , 42 , 97 ]. It is well known that biostimulants, especially seaweed extracts, can increase crop development, even in stress conditions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation